Synchronous Multicentric Giant Cell Tumour of Distal Radius and Sacrum with Pulmonary Metastases - Varun Sharma Tandra; Krishna Mohan Reddy Kotha; Moorthy Gadisetti Venkata Satyanarayana; Kali Varaprasad Vadlamani; Vyjayanthi Yerravalli (Case Reports in Oncological Medicine)
Giant cell tumour (GCT) is an uncommon primary bone tumour, and its multicentric presentation is exceedingly rare. We report a case of a 45-year-old female who presented to us with GCT of left distal radius. On the skeletal survey, osteolytic lesion was noted in her right sacral ala. Biopsy confirmed both lesions as GCT. Pulmonary metastasis was also present. Resection-reconstruction arthroplasty for distal radius and thorough curettage and bone grafting of the sacral lesion were done. Multicentric GCT involving distal radius and sacrum with primary sacral involvement is not reported so far to our knowledge.